PLAGL1: an important player in diverse pathological processes - Vega Benedetti A.F. (2016)
The PLAGL1 gene encodes a homonymous zinc finger protein that promotes cell cycle arrest and apoptosis through multiple pathways. The protein has been implicated in metabolic, genetic, and neoplastic illnesses, but the molecular mechanisms by which the protein PLAGL1 participates in such diverse processes remains to be elucidated. In this review, we focus mainly on the molecular biology of PLAGL1 and the relevance of its abnormalities to several pathological processes.